A review of the genus Dryocoetiops Schedl, with new species, new synonymy and a key to species (Coleoptera: Curculionidae: Scolytinae) - Beaver, Roger A.; Smith, Sarah M.; Sanguansub, Sunisa (Zootaxa, 2019)
Eighteen species currently placed in the genus Dryocoetiops Schedl, 1957, are reviewed. Two new species are described: Dryocoetiops pasohensis Beaver, Smith and Sanguansub, D. salebrosus Beaver, Smith and Sanguansub. The following new synonymy is proposed: Dryocoetiops apatoides (Eichhoff, 1875) (= Taphrorychus striatus Nobuchi, 1966, syn. n.); Dryocoetiops moestus (Blandford, 1894) (= Dryocoetes australis Schedl, 1942, syn. n., Dryocoetes coffeae Eggers, 1923, syn. n., = Dryocoetes dinoderoides Blandford, 1894, syn. n., = Dryocoetes eugeniae Schedl, 1942, syn. n., = Dryocoetes hirsutus Schedl, 1939, syn. n., = Dryocoetes javanus Eggers, 1936, syn. n., = Dryocoetes malaccensis Schedl, 1942, syn. n., = Pseudopoecilips taradakensis Murayama, 1957, syn. n., = Dryocoetes tonkinensis Schedl, 1942, syn. n.); Dryocoetiops semigranulatus (Eggers, 1936) (= Dryocoetes kepongi Schedl, 1953, syn. n.). The following new combinations are proposed: Coccotrypes flavicornis (Blandford, 1895) comb. n.; Procryphalus petioli (Beaver, 1990) comb. n., both from Dryocoetiops. A key is provided to the females of ten species remaining in Dryocoetiops; males remain unknown in the genus. The taxonomy, distribution and biology of the species are briefly reviewed, and some new distributional records included.